Structure-based discovery and experimental validation of HIT101481851 as a potential PKMYT1 inhibitor for pancreatic cancer - Wang, Ting; Wang, Jingyu; Yao, Gongxiong; Zhang, Hongchao; Song, Chenghui; Ao, Xueren (Frontiers in Pharmacology, 2025)
PKMYT1 is a validated therapeutic target in pancreatic cancer due to its critical role in controlling the G2/M transition of the cell cycle. In this study, a structure-based drug discovery pipeline was implemented to identify novel PKMYT1 inhibitors with high binding stability and anticancer potential. Pharmacophore models were constructed from four PKMYT1 co-crystal structures, and virtual screening was performed against a large compound library. Through molecular docking and intersection analysis, five consensus high-affinity compounds were identified, among which HIT101481851 demonstrated the most favorable binding characteristics. Molecular dynamics simulations confirmed its stable interactions with key residues such as CYS-190 and PHE-240 across multiple PKMYT1 conformations. ADMET predictions indicated good gastrointestinal absorption, acceptable drug-likeness, and low risk of off-target reactivity. Furthermore, in vivo experiments showed that HIT101481851 inhibited the viability of pancreatic cancer cell lines in a dose-dependent manner while exhibiting lower toxicity toward normal pancreatic epithelial cells. These results suggest that HIT101481851 is a promising lead compound for the development of PKMYT1-targeted therapeutics in pancreatic cancer.